Фольклорна проза "Калинівського чуда". Проблема сюжетотворення і руху тексту - Дяків, В. (Народна творчість та етнографія, 2006)
The article discusses the problem of folklore prose of "Kalynivske Chudo". The researches allow distinguishing the main repertoire of the stories. The collection includes prose on religious topics that formed in 1920s, mostly by the pilgrims to the Cross of Kalynivka (present Vinnytsya region). All the stories comprise several similar features in plot (pilgrimage, miracles of the Cross, motives of Mother and Son at the Cross, etc.) and characters (Jesus Christ, the Virgin, angels, etc.). The folklore of "Kalynivske Chudo" was one of the brightest manifestations of the powerful wave of folk religion in that time Ukraine.